Bolivia : Second Review Under the Stand-By Arrangement and Request for Waiver of Applicability and Modification of Performance Criteria-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2004)
Bolivia's pursuit of structural reforms has begun to yield results despite the difficult social and political context. The fiscal performance under the program needs to be substantially strengthened. The recent passage of the informal corporate workout law represents a substantial advance in financial and corporate restructuring. Executive Directors are in agreement with the government on the approach to reduce banking system fragility. To sustain economic growth, the pace of structural reforms has to be invigorated. Firm implementation of the program can achieve its goals.